The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/14651858.cd004333.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Helmets for preventing injury in motorcycle riders

Abstract: Motorcycle helmets reduce the risk of death and head injury in motorcycle riders who crash. Further well-conducted research is required to determine the effects of helmets and different helmet types on mortality, head, neck and facial injuries. However, the findings suggest that global efforts to reduce road traffic injuries may be facilitated by increasing helmet use by motorcyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
135
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(154 citation statements)
references
References 68 publications
4
135
1
3
Order By: Relevance
“…However, this study indicates that helmet use among MRV users may not be associated with a reduction in severe head injuries and intracranial hemorrhage. Although these findings are inconsistent with existing literature that indicates that helmet use reduces risk of MRV-related death and head injury [18,19], other studies confirm that helmets offer insufficient protection for MRV participants [1][2][3]. This study adds to existing literature by indicating that, even among a cohort of patients with higher rates of compliance with safety equipment use, serious injuries associated with significant morbidity still occur frequently.…”
Section: Discussioncontrasting
confidence: 73%
“…However, this study indicates that helmet use among MRV users may not be associated with a reduction in severe head injuries and intracranial hemorrhage. Although these findings are inconsistent with existing literature that indicates that helmet use reduces risk of MRV-related death and head injury [18,19], other studies confirm that helmets offer insufficient protection for MRV participants [1][2][3]. This study adds to existing literature by indicating that, even among a cohort of patients with higher rates of compliance with safety equipment use, serious injuries associated with significant morbidity still occur frequently.…”
Section: Discussioncontrasting
confidence: 73%
“…The importance of the helmet and its role in preventing head injuries and deaths has been discussed by many scholars (Evans, Frick 1988;Wilson 1989;Gabella et al 1995;Rowland et al 1996;Lin et al 2001;Liu et al 2004). Many studies have identified head injuries can contribute to an astonishingly high percentage of motorcycle accidents with a fatal outcome, even up to 60% (Azhar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The protection which this confers on the motorcycle user is demonstrated in the literature, potentially reducing by up to 42% the mortality rates in traffic accidents for motorcyclists, and reducing the risk of head trauma by up to 69%. 13 Of the 178 countries analyzed in the Global status report on road safety: time for action, a 40% have laws requiring motorcyclists, both drivers and passengers, to wear helmets. The importance of standardizing and regulating helmet use is also noteworthy, as well as their correct adjustment.…”
mentioning
confidence: 99%